Nilai Pendidikan Karakter Dalam Novel Si Anak Savana Karya Tere Liye Dan Implikasinya Pada Pembelajaran Sastra Di SMA - Episiana Sari; Misnawati Misnawati; Lazarus Linarto; Petrus Poerwadi; Ibnu Yustiya Ramadhan (Universitas Palangka Raya, 2023)
This study aims to describe (1) the value of character education in Tere Liye's Novel Si Anak Savana (2) the implications for learning literature in high school.This study uses qualitative methods and types of library research. Qualitative research was used to describe the value of character education in Tere Liye's Novel Si Anak Savana and to describe its implications for teaching literature in high school. The results of the study were 14 values of character education and 28 quotes of character education values in Tere Liye's novel Si Anak Savana by Tere Liye. The 14 values of character education are: (1) Religious (form: obedient to worship, always pray, be grateful, believe, put your trust in and pray). (2) Honest (form: not lying) (3) Discipline (form: not delaying work). (4) Hard Work (its form: always trying and never giving up), (5) Independent (its form: not depending on other people) (6) Creative (its form: always having ideas and ideas) (7) Democratic (its form: expressing opinions ) (8) Curiosity (its form: curiosity), (9) Friendly (its form: always doing work together), (10) Peace-loving (its form: not wanting to fight), (11) Caring for the environment (its form : environmental cleanliness and natural preservation), (12) Social care (its form: helping others and social service). (13) Likes to read (form: likes to read) (14) Responsibility (form: obligation that must be carried out. The most dominant character education value in Tere Liye's novel Si Anak Savana by Tere Liye is the value of social care character education, and curiosity From the results of the analysis of the 28 values of character education in Tere Liye's novel Si Anak Savana, it can be implicated in teaching literature in class XI high school, according to KD 3.20 analyzing the messages from the two fiction books (novels and poetry) that have been read. , students can learn the value of character education.Students can also find the value of character education in novel.